OXIDATIVE STRESS AND ALTERED LEVELS OF ANTIOXIDANTS IN ADOLESCENTS WITH DOWN SYNDROME DURING PRE-EXERCISE AND POST-EXERCISE - Arslan, Cengiz; Ozbey, Ulku; Erisir, Mine; Seyran, Ayse; Savucu, Yuksel (John Wiley & Sons Inc, 2009)
[Abstract Not Available]